Pheochromocytoma/paraganglioma: recent updates in genetics, biochemistry, immunohistochemistry, metabolomics, imaging and therapeutic options - Antonio, Karren (Gland Surg, 2020)
Pheochromocytomas and paragangliomas (PPGLs), rare chromaffin/neural crest cell tumors, are commonly benign in their clinical presentation. However, there are a number of cases presenting as metastatic and their diagnosis and management becomes a dilemma because of their rarity. PPGLs are constantly evolving entities in the field of endocrinology brought about by endless research and discoveries, especially in genetics. Throughout the years, our knowledge and perception of these tumors and their genetic background has greatly expanded and changed, and each new discovery leads to advancement in the diagnosis, treatment and follow-up of PPGLs. In this review, we discuss the recent updates in the genetics, biochemistry, immunohistochemistry, metabolomics, imaging and treatment options of PPGLs.